Implementasi Akad Muzara'ah dalam Pertanian Bawang Merah di Kabupaten Enrekang - Lasri, Nurannisa; Amir, Rahma; Qayum, Abdul Rahman (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
The main problem of this research is how the Implementation of Muzara'ah Akad on Shallot Farmers with Landowners in Tomenawa Village, Baraka District, Enrekang Regency (Urf Analysis). This problem is then broken down into sub-problems, namely How is the Muzara'ah Akad Process on Shallot Farmers with Landowners in Tomenawa Village, Baraka District, Enrekang Regency? and How is the Role of Landowners with Cultivators in Supporting the Community Economy in Tomenawa Village, Baraka District, Enrekang Regency? This type of research is qualitative descriptive research with a legal sociology approach. The data sources in this research are primary data as many as 5 sources namely Mr. Najamuddin, Mr. Sainuddin, Mr. Ardi, Mr. Agung, and Mr. Yusran. The data collection techniques used are interviews, observation and documentation. The results showed that the process of the muzara'ah contract on shallot farmers in Tomenawa Village, Baraka Subdistrict, Enrekang Regency carried out between the landowner and the farmer is that the landowner hands over his land to the farmer to be cared for and maintained then gets a share of the shallot land according to the agreement at the beginning of the contract. Then the role of landowners with tenant farmers in supporting the community's economy is that landowners provide land resources for agriculture, while tenant farmers use their skills and energy to manage agricultural land. Both contribute to the production of food and agricultural commodities, create jobs, and increase the income and welfare of people in agricultural areas. The implication of this research is that as information to the local government, it can be followed up with various regional policies in price stability, especially the price of drugs such as KCL, ZA, and urea which are expensive compared to the results obtained by farmers in shallot farming. For the community in the muzara'ah contract, a cooperation agreement should be made in writing, because if there are deviations in the future, it can be resolved with clear evidence.